Bala and Ojas Promoting Factors Quoted in Caraka Samhita - Gangwar, Akanksha; Yadav, S S (International Research Journal of Ayurveda & Yoga, 2021)
With increasing globalization and industrialization, the life of human beings has become much more sedentary, technology dependent and full of rush and hustle because of which humans are gradually becoming unhealthier and more diseased than ever before. Today, everyone is in hurry so they want everything to be quick and speedy. They don’t have time to spend upon thinking about eating healthy and lead a healthy lifestyle; which eventually made them fell ill and get various kinds of diseases. Vyadhikshamatwa is a simple term which means body’s own capacity to resist various kind of diseases. It is related to bala as well as ojas as mentioned in ayurveda. Bala is characteristic feature of healthy physical and mental state of body. As the aim of ayurveda is to make an unhealthy person disease free and to maintain the health of a healthy person. So, by choosing a healthy diet and lifestyle one can not only become disease free but can also lead a long and healthy life as well. Various bala, ojas and vyadhikshamatwa promoting factors are mentioned in Ayurvedic texts which acts directly or indirectly upon human body. This article is the compilation of bala, ojas and vyadhikshamatwa promoting factors